CROSSING THE BAR: A COMPARATIVE ANALYSIS OF THE DOSTOEVSKIAN ELEMENTS AND INFLUENCES IN JOAQUIN’S FICTION - Oamil, Erwin Ligsay (PEOPLE: International Journal of Social Sciences, 2019)
This paper expounds how deep the great Russian fictionist Fyodor Dostoevsky had influenced his Filipino counterpart Nick Joaquin’s own works by applying comparative method of research. Sixteen (16) “Dostoevskian” elements and influences are found evident in Joaquin’s representative works, which further validate the Russian master’s timeless and universal relevance to the literary tradition. Joaquin for his part is already a titan of Philippine Literature, in his own respect, particularly in the English medium. His magnitude, however, can be tested further through the Dostoevskian standard, which is often used in comparison to the creative powers of other writers. By and large, this study contributes to the growth of comparative literature and Philippine studies. More wittingly, it can strengthen the understanding that the creative process of literary art extends to the other spheres of human expression, such as philosophy, history, religion, and psychology, even culture.